Assistance In Preparing Financial Statements On Umkm Sahabat In Nagori Karang Bangun Huta Iv, Siantar District, Simalungun Regency - Elly Susanti; Khairul Azwar; Christine D. Nainggolan; Astuti; Ernest Grace (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
The purpose of this community service activity is to provide understanding, skills and knowledge in the preparation of financial statements. This community service was conducted at UMKM Sahabat in Nagori Karang Bangun Huta IV, Siantar District, Simalungun Regency. The method of implementation of this activity is carried out using the method of action research activities. The service team conducted activities consisting of two activities, namely the supply of financial report preparation instruments as well as training workshops on the preparation of financial statements. This assistance is done with a sense of kinship so that this assistance runs smoothly, relaxed, directed and the material remains mastered by partners with interactive discussion mentoring methods